The impact of HIV self-testing on risk behaviors among men who have sex with men: a mixed-methods study - Su, Rong; Liu, Yi; Li, Peilong; Ge, Lin; Liao, Meizhen; Fu, Yong; Song, Xin; Shan, Duo; Tang, Houlin; Li, Dongmin (Frontiers in Public Health, 2024)
Background: Men who have sex with men (MSM) have a high prevalence of HIV and a low rate of HIV testing in China. HIV self-testing (HIVST) presents a viable strategy for expanding HIV testing among MSM. However, the impact of HIVST on risk behaviors among MSM remains controversial.Our study sought to ascertain this impact. Methods: From April 2021 to January 2022, a mixed-methods study was conducted in Qingdao City, employing both quantitative and qualitative methodologies. The quantitative component entailed a cohort study among MSM who had used HIVST. Generalized estimating equations fitting Poisson regressions were used to analyze the changes in risk behaviors of MSM in short time after HIVST (ST-HIVST)during and longer time after HIVST (LT-HIVST)after HIVST compared to before HIVST.Subsequently, we conducted in-depth interviews with 18 MSM who completed the follow-up to delve deeper into the impact of HIVST on MSM.Results: A total of 410 MSM were recruited in the cohort, of whom 83 were lost to follow-up.Compared to before HIVST, there were no significant changes in risk behaviors in ST-HIVSTduring HIVST (P>0.05), while the proportion of recreational drugs abuse (20.7% vs 33.3%), commercial sex (14.6% vs 22.9%), and unprotected anal sex (95.9% vs 98.5%) increased significantly in LT-HIVSTafter HIVST (P<0.05). Specific changes varied across demographic characteristics. According to qualitative interviews, MSM might have decreased risk perception and increased risk behaviors after HIVST.The use of HIVST may promote MSM to engage in risk behaviors. In the future, customized HIVST promotion programs need to be developed to expand HIV testing among MSM and simultaneously control their risk behaviors.